Functional Outcome and Safety of Intracranial Thrombectomy After Emergent Extracranial Stenting in Acute Ischemic Stroke Due to Tandem Occlusions - Bücke, Philipp; Aguilar Pérez, Marta; AlMatter, Muhammad; Hellstern, Victoria; Bäzner, Hansjörg; Henkes, Hans (Frontiers in Neurology, 2018)
Background and Purpose: Various endovascular approaches to treat acute ischemic stroke caused by extra- intracranial tandem occlusions (TO) exist: percutaneous transluminal angioplasty with or without emergent extracranial carotid stenting (ECS) due to high-grade stenosis preceded or followed by intracranial mechanical and/or aspiration thrombectomy (MT). Which treatment strategy to use is still a matter of debate. Methods: From our ongoing prospective stroke registry we retrospectively analyzed 1071 patients with anterior circulation stroke getting endovascular treatment within six hours of symptom onset. ECS prior to intracranial MT for TO (n=222) was compared to MT as standard of care (control group; acute intracranial vessel occlusion without concomitant ipsilateral ICA-occlusion or high-grade stenosis [C; n=849]). Good functional outcome (mRS ≤ 2 at 3 months), mortality rates, frequencies of symptomatic intracranial hemorrhage (sICH) and successful recanalization (Thrombolysis in Cerebral Infarction Score [TICI] 2b or 3) were assessed. In subgroup analyses we tried to detect possible influences of stroke etiology, dual inhibition of platelet aggregation (IPA; clopidogrel [CLO]: n=83; ticagrelor [TIC]: n=137; in combination with Aspirin) and intravenous thrombolysis (IVT). Results: Functional outcome was superior in TO (mRS 0-2: 44.6%) when compared with controls (36.0%; (OR [95% CI]: 3.49 [1.59-7.67];p=0.002). There was no difference in all-cause mortality at three months (TO: 21.6%; C: 27.7%; 0.78 [0.47-1.29;p=0.324), in-hospital mortality (0.76 [0.45-1.30; p=0.324), sICH (TO: 3.2%; C: 5.0%; 0.70 [0.30-1.59;p=0.389) and TICI 2b/3 (TO: 89.1%; C: 88.3%; p=0.813). In subgroup-analysis, TIC and CLO did not differ in functional outcome (TIC: 45.3%; CLO: 44.6%; 1.04 [0.51-2.09]; p=0.920) and mortality rates (all-cause mortality: TIC: 23.4%; CLO: 16.9%; 0.75 [0.27-2.13]; p=0.594). sICH was more frequent in TIC (n=7 [5.1%]) versus CLO (n=0; p=0.048). Conclusion: In our pre-selected cohort, ECS prior to intracranial MT in TO allowed for a good functional outcome that was superior compared to a control population. Mortality rates did not differ. Despite a dual IPA in TO, there was no increase in sICH. CLO and TIC for dual IPA did not differ in terms out outcome and mortality rates. A significant increase in sICH was observed after initial loading with TIC.